Marriage and the Devil: The Literary Exchange, Values, and Power Structures of Franz Kafka and Milena Jesenská - Lucyna Darowska (Humanities)
The article examines the inspiring relationship between the well-known Prague journalist Milena Jesenská and the world-famous writer Franz Kafka—authors of different genres who shared reflections on being human, the world, religion, and prose. It elaborates on the commonalities and the divisions, the mutual admiration as well as the irreconcilable differences, which can also be mapped onto selected works by both authors. In her articles, Jesenská criticizes social and political issues, elaborating a normative position, in the sense of describing the stance, attitudes, and politics that are needed for change. Kafka’s position, as if complementary to Jesenská’s, shows only this human world. On the basis of some of their letters, articles, and prose works, this article examines the relationship between the two authors and the textuality of their relationship, as well as their shared and different values in the contexts of various power relations.